Current‐dependent ocular tilt reaction in deep brain stimulation of the subthalamic nucleus: Evidence for an incerto‐interstitial pathway?. (3rd February 2022) - Friedrich, Maximilian U.; Eldebakey, Hazem; Roothans, Jonas; Capetian, Philipp; Zwergal, Andreas; Volkmann, Jens; Reich, Martin
Abstract: Background and purpose: The aim was to characterize a combined vestibular, ocular motor and postural syndrome induced by deep brain stimulation (DBS) of the subthalamic nucleus in a patient with Parkinson's disease. Methods: In a systematic DBS programming session, eye, head and trunk position in roll and pitch plane were documented as a function of stimulation amplitude and field direction. Repeat ocular coherence tomography was used to estimate ocular torsion. The interstitial nucleus of Cajal (INC), zona incerta (ZI) and ascending vestibular fibre tracts were segmented on magnetic resonance imaging using both individual and normative structural connectomic data. Thresholded symptom‐associated volumes of tissue activated (VTA) were calculated based on documented stimulation parameters. Results: Ipsilateral ocular tilt reaction and body lateropulsion as well as contralateral torsional nystagmus were elicited by the right electrode in a current‐dependent manner and subsided after DBS deactivation. With increasing currents, binocular tonic upgaze and body retropulsion were observed. Symptoms were consistent with an irritative effect on the INC. Symptom‐associated VTA was found to overlap with the dorsal ZI and the ipsilateral vestibulothalamic tract, while lying rather distant to the INC proper. A ZI‐to‐INC 'incerto‐interstitial' tract with contact to the medial‐uppermost portion of the VTA could be traced. Conclusion: Unilateral stimulation of INC‐related circuitry induces an ipsilateral vestibular, ocular motor and postural roll‐plane syndrome, which converts into a pitch‐plane syndrome when functional activation expands bilaterally. In this case, tractography points to an incerto‐interstitial pathway, a tract previously only characterized in non‐human primates. Directional current steering proved useful in managing this rare side effect. Abstract : A combined vestibular, ocular motor and postural syndrome induced by deep brain stimulation (DBS) of the subthalamic nucleus in a patient with Parkinson's disease is described. Although its complex phenomenology is consistent with irritation of the interstitial nucleus of Cajal (INC), magnetic resonance imaging revealed the symptom‐associated 'volume of tissue activated' (VTA) by DBS to be localized rather distant to the INC proper. Ultimately, a zona incerta to INC, 'incerto‐interstitial' tract, with contact to the medial‐uppermost portion of the VTA could be implicated in this syndrome.